Young creative writers discovered! - Noraisah Nurul Fatwa, Mohd Razali (Pusat Bahasa Moden dan Sains Kemanusiaan, 2012)
6 November 2012. As part of the project for UMP’s cluster schools, an English Creative Writing Workshop was held at the Banquet Hall, Chancellery. A group of 39 form 3 students from SMK Seri Pekan accompanied by 3 teachers participated in the workshop. The students were given a task to create their own groups and named them based on the character of 7 monsters in order to develop their own creativity.